Arrest History Among Men and Sexual Orientation - Fisher, Dennis G.; Milroy, Michael E.; Reynolds, Grace L.; Klahn, Jennifer A.; Wood, Michele M. (Crime & delinquency, 2004)
This study explored associations between ever having been arrested and other variables among 490 male drug users. Participants were classified into three groups based on recent sexual history: men who had not had sex (NOSEX), men who had had sex with women (HETERO), and men who had had sex with men (MSM). We found that MSM who had been arrested were more likely to have had syphilis and gonorrhea, exchanged sex for either drugs or money, and exchanged money or drugs for sex. Given concerns about the syphilis epidemic in California among MSM, we recommend that correctional facilities engage in a vigorous syphilis-screening program. [ABSTRACT FROM AUTHOR]